Determinação dos parâmetros de resistência, "Creep" e de Relaxação de Tensões de uma argila mole do Rio de Janeiro - Vilela, Tiago Franco (1976)
Determining the geotechnical characteristics of a layer of soft clay. The influence of the organic matter on the consistency index is discussed. The compressibility of this clay is compared to that of other clays as these of the "Baixada Fluminense" and these of "Santos" and the effect of the preconsolidation pressure is analysed. The stress-strain curves of the triaxial tests are represented by the hyperbolic formula. The strength and stress-strain parametersare determined and compared with those of other clays. The results of triaxial tests performed on undisturbed and disturbed samples are discussed. The stress-strain-time relationships are studied using results of creep and stress-relaxation tests performed in undrained conditions. Finally conditions are drawn concerning the geotechnical parameters which would be of more interest for the design of a deep excavation in this clay.